Expectativas de atuação profissional de formandos em pedagogia - Sousa, Paula Frassinetti da Silva (1976)
The purpose of the present paper, a descriptive - exploratory research about 'Role Professional Expectatioons of a Group Graduate Students in Education', was specially aimed toward the appraising of courses offered by the School of Ecucation (Faculdade de Educação da Universidade do Maranhão - FACED, UMa), where different specializations could be chosen (undergraduate level), compared with work opportunities.